EFISIENSI DAN ENERGETIKA PENETASAN KISTA ARTEMIA (Artemia salina) PADA SALINITAS MEDIA YANG BERBEDA - Endah Heryastuti; Sutrisno Anggoro; Subandiyono Subandiyono (Universitas Gadjah Mada, 2016)
Hatching rate of Artemia salina cysts in the hatching process is variable due to many factors. Osmolarity of the medium is one of the factors determining hatching process of A. salina cysts. The purpose of this study is to assess the hatching process of A. salina cysts in a various osmotic condition on the hatching energetics efficiency and rate. The experimental design used was a 2 x 5 factorial completely randomized design. The first factor is an addition of chlorine (non-decapsulation and decapsulation) and the second factor is osmolarity of medium (640.27; 787.02; 901.76; 1080.51 and 1227.25 mOsm.L-1H2O). The results showed that hatching of A. salina cyst on various osmotic condition has significantly differed the hatching rate. No significant differences in the hatching energetics efficiency were obtained from each experimental groups. Media with osmolarity level of iso-osmotic to hyperosmotic (901.76-1227,25 mOsm.L-1H2O) provides a high hatching rate. Energetics efficiency of artemia cysts hatching is ranged from 640.27 to 1227.25 mOsm.L-1H2O in both hypoosmotic, isosmotic and hyperosmotic media.